Kosovo Public Finance Review : Fiscal Policies for a Young Nation - World Bank (Washington, DC, 2014)
Kosovo is Europe s youngest country, both in terms of history and demographics. As part of the former Yugoslavia, Kosovo became a separate territory under United Nations administration in 1999, and declared its independence in 2008. By February 2014 it had been recognized by 106 UN member states including 23 out of 28 EU members. Kosovo is a potential candidate for European Union (EU) membership and is currently negotiating a Stabilization and Association Agreement (SAA) with the European Commission. From 1999 Kosovo has been using the Deutsche Mark and, since 2002, its successor currency, the Euro, as legal tender. Kosovo is a landlocked country in South East Europe (SEE) with about 1.8 million inhabitants and a large migrant population based mainly in Western European countries. Kosovo has taken great strides to rebuild an economy destroyed by the collapse of Yugoslavia and the 1998-99 war, with sound fiscal numbers and budgets focused on capital expenditure. In general, Kosovo s headline macroeconomic indicators are also relatively sound. Growth has averaged over 4 percent since 2000 and remained positive after 2008 during the global crisis years. Household survey evidence for 2006-11 suggests that economic growth benefitted all sections of society but the poorest 40 percent of the population saw consumption rise faster than wealthier groups. Public and private investments have made large contributions toward economic growth over the last five years as efforts to rebuild the economy continued.